Penerapan Sistem Moneter Islam Di Lembaga Koperasi Kartini Desa Wanakerta Kecamatan Cibatu Kabupaten Garut - Burhanudin , Ujang; Sunarsa, Sasa; Mubarokah, Ismi Latifah (Jurnal Hukum Ekonomi Syariah, 2024)
Abstract This article discusses the potential implementation of the Islamic monetary system in cooperative institutions. The Islamic monetary system has different characteristics from the conventional monetary system, namely prioritizing sharia principles such as the prohibition of usury, gharar, and maysir. The implementation of the Islamic monetary system in cooperatives can provide double benefits. On the one hand, cooperatives can carry out economic activities in accordance with Islamic values. On the other hand, the sharia monetary system can strengthen the role of cooperatives as a people-based economic institution that aims to achieve the welfare of members and society. The type of research used is qualitative research, case studies on cooperative institutions that implement the Islamic monetary system. This article explains how cooperative products, services, and governance need to be adjusted to align with sharia principles. In addition, challenges and opportunities in the implementation of the Islamic monetary system in cooperative institutions were also discussed. In conclusion, the implementation of the Islamic monetary system in cooperatives has the potential to realize fair, ethical, and common welfare-oriented economic practices. Keywords: Monetary system; Application of Islamic principles; Cooperation